Pengaruh Pijat Kaki dan Rendam Air Hangat Campur Kencur terhadap Edema Kaki pada Ibu Hamil di Klinik Satria Mekar - Ade Nur Setianingsih; Achmad Fauzi (Universitas Malahayati Lampung, 2022)
ABSTRACT Leg edema is found in about 80% of pregnant women in the third trimester, which occurs due to uterine flexion which inhibits venous return and the pull of gravity which causes greater fluid retention. Leg edema if left untreated can cause discomfort, a feeling of heaviness, and cramping at night. So foot edema must be treated. One of them is by non-pharmacological methods, namely by foot massage and warm footbath with aromatic ginger. This study aims to analyze the effect of foot message and warm footbath with aromatic ginger on foot edema among pregnant woman in klinik satria mekar 2022. To determine the effect of foot message and warm footbath with aromatic ginger on foot edema among pregnant woman in klinik satria mekar 2022. This quast-experimental study used a one group pretest and posttest design. The sample in this study were pregnant women with leg edema as many as 20 people, the sampling technique was purposive sampling. The instrument uses the SOP and the pitting scale observation sheet. The data were analyzed using the Wiloxcon test. Univariate analysis showed that the average degree of leg edema before the intervention was grade 3+ and after the intervention was grade 1+. Bivariate analysis showed that there was an effect of foot message and warm footbath with aromatic ginger on foot edema among pregnant woman p-value 0.05.The effect of foot message and warm footbath with aromatic ginger on foot edema among pregnant woman.it is expectedIt is hoped that health workers can apply and teach foot massage therapy and soak warm water mixed with kencur in pregnant women who experience leg edema. Keywords: Foot Edema, Pregnant Women, Foot Message ABSTRAK Edema kaki ditemukan sekitar 80% pada Ibu Hamil trimester III, yang terjadi akibat penekukan uterus yang menghambat aliran balik vena dan tarikan gravitasi yang menyebabkan retensi cairan semakin besar. Edema kaki jika tidak ditangani dapat menyebabkan ketidaknyamanan, perasaan berat, dan kram dimalam hari. Sehingga edema kaki harus ditangani. Salah satunya dengan cara non-farmakologis yaitu dengan cara pijat kaki dan rendam air hangat campur kencur. Penelitian ini bertujuan untuk menganalisis pengaruh pijat kaki dan rendam air hangat campur kencur pada ibu hami di Klinik Satria Mekar. Mengetahui pengaruh pijat kaki dan rendam air hangat campur kencur terhadap edema kaki pada ibu hamil di klinik satria mekar tahun 2022. Penelitian quast-experiment ini menggunakan rancangan one group pretest dan posttest design. Sampel dalam penelitian ini adalah ibu hamil dengan edema kaki sebanyak 20 orang, teknik pemgambilan sampel yaitu purposive sampling. Instrumen menggunakan SOP dan lembar observasi pitting scale. Data di analisis dengan menggunakan uji wiloxcon. Analisis univariat menunjukan rata-rata derajat edema kaki sebelum intervensi adalah derajat 3+ dan setelah intervensi derajat 1+. Analisis bivariat menunjukkan adanya pengaruh pijat kaki dan rendam air hangat campur kencur terhadap edema kaki pada ibu hamil p-value 0,05. Adanya pengaruh pijat kaki dan rendam air hangat campur kencur terhadap edema kakim pada ibu hamil. Diharapkan tenaga kesehatan, dapat menerapkan maupun mengajarkan terapi pijat kaki dan rendam air hangat campur kencur pada ibu hamil yang mengalami edema kaki. Kata Kunci: Edema kaki, Ibu hamil, Pijat Kaki